The participation of people with physical motor disabilities in teaching and learning in Higher Education in El Salvador (Educational Knowledge, 2021)
This study addresses the participation of people with physical disabilities in the teaching and learning process of Salvadoran higher education, focusing solely on the influence of educational policies, teacher training, and the concept of educability. This literature review demonstrates that the evaluation methods used in educational systems structurally determine the scope of educational policies. It also highlights the need to conceive of teacher training based on inclusive models and the importance of considering educability in educational policies and its impact on social policies.Therefore, the study proposes participatory actions to shift the perspective on education and achieve adequate participation for this group. These actions should include developing technical and soft skills in the training of future teachers and fostering inclusive attitudes toward people with physical disabilities. It is also necessary to update the curricula of educational programs.
Keywords: Participation; physical motor disability; Higher Education